Problemas en el proceso de aprendizaje de la lectura en los niños/as de cuarto año del Centro de Educación Básica Intercultural Bilingüe Antonio Millingalli Ayala de la Comuna Sarahuasi, Parroquia Chugchilan, Cantón Sigchos, en el año lectivo 2011 -2012 - Vaca Ayala, Luis Jorge (2015)
This study presents an exploratory analysis to have an approach to the educational reality, in order to gather information to recognize situations and problems of fourth grade teachers regarding reading. Method, or constructivist approach in teaching reading is exposed. At the same time, it appears that in the educational tradition, the problem of teaching and learning of reading has been proposed as a methodological issue; that is, it discusses the advantages and disadvantages in using this or that method. Thus, solutions or alternatives in this regard have focused on methodological proposals are interpreted and adapted by teachers to their knowledge and experience; we would say that have resulted in prescription thereby producing repetitive teaching and learning and mechanistic where the teacher and students become, respectively, suppliers and consumers of other texts without the possibility of adopting reflective and critical attitudes, which has affected the low quality and reading performance in the fourth year of the Center for Intercultural Bilingual Elementary Education "Millingalli Ayala Antonio"